Cardiac, possible cardiac, and likely non-cardiac origin of chest pain: a hitherto underestimated parameter in German chest pain units - Imhof, Sebastian; Hochadel, Matthias; Konstantinides, Stavros; Voigtländer, Thomas; Schmitt, Claus; Nowak, Bernd; Rassaf, Tienush; Senges, Jochen; Münzel, Thomas; Giannitsis, Evangelos; Breuckmann, Frank (Herz, 2024)
Current guidelines emphasize the diagnostic value of non-cardiac or possibly cardiac chest pain. The goal of this analysis was to determine whether German chest pain units (CPUs) adequately address conditions with “atypical” chest pain in existing diagnostic structures.
Gesehen am 13.03.2024